Berberine Attenuates Chronic Atrophic Gastritis Induced by MNNG and Its Potential Mechanism - Tong, Yuling; Liu, Liping; Wang, Ruilin; Yang, Tao; Wen, Jianxia; Wei, Shizhang; Jing, Manyi; Zou, Wenjun; Zhao, Yanling (Frontiers in Pharmacology, 2021)
The purpose of this study was to investigate the therapeutic effect of berberine (BBR) on MNNG-induced chronic atrophic gastritis (CAG) and the possible mechanism of BBR through TGF-β1/PI3K signal pathway. GES-1 were pretreated with MNNG for 2 h before BBR treatment in all procedures. Cell viability was quantified by cell counting kit-8, and GES-1 morphology and proliferation were detected by high content screening (HCS) assay. The rat model of CAG was established by MNNG, and the therapeutic effect of BBR on stomach histopathology and serum supernatant were analyzed in vivo. In addition, the possible mechanism of BBR was further discussed, and the expression of related genes and proteins in TGF-β1/PI3K signal pathway was detected. The results showed that BBR could significantly improve the survival rate and morphological changes of GES-1, improve the gastric tissue injury of CAG rats, and reduce the expression of G-17 and inflammatory factors IL-8, TNF-α, IL-6 and IL-1β. In addition, BBR down-regulated the expression of TGF-β1 axis-related signals such as TGF-β1, PI3K, p-Akt/Akt, p-mTOR/mTOR and P70S6K, and promoted the expression of PTEN, LC3-II and Beclin-1. In Conclusion, BBR can improve CAG which may be closely related to TGF-β1/PI3K signal pathway.